2010
DOI: 10.1111/j.1365-2095.2010.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary mannan oligosaccharide on the survival, growth, immunity and digestive enzyme activity of freshwater crayfish, Cherax destructor Clark (1936)

Abstract: The aim of this experiment was to determine the effects of dietary supplementation of Bio‐Mos® as a source of mannan oligosaccharide (MOS) on the growth, survival, immunity and digestive enzyme activity of freshwater crayfish, Cherax destructor (yabby). A basal diet and another diet with 0.4% of Bio‐Mos® supplemented to the basal diet were formulated. Each diet was provided to eight yabbies (35.14 ± 0.48 g, initial weight) replicated 3 times in individual 250‐L plastic cylindrical tanks for a duration of 56 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 31 publications
7
44
0
6
Order By: Relevance
“…(Sun et al 2011), in beluga (Huso huso) and Persian sturgeon (Acipenser persicus) by lactic acid bacteria (LAB) (Askarian et al 2011), in grouper (E. coioides) by Lactococcus lactis and E. faecium (Sun et al 2011), and in artemia (Artemia urmiana) by B.subtilis and B. licheniformis (Ahmadnia Motlagh et al 2012). Similar results have also been reported in previous studies on prebiotics in fresh water crayfish (Cherax destructor) fed mannan oligosaccharides (MOS) (Sang et al 2011) and Caspian roach (Rutilus rutilus) fingerlings fed fructooligosaccharides (FOS) (Soleimani et al 2012).…”
Section: Discussionsupporting
confidence: 77%
“…(Sun et al 2011), in beluga (Huso huso) and Persian sturgeon (Acipenser persicus) by lactic acid bacteria (LAB) (Askarian et al 2011), in grouper (E. coioides) by Lactococcus lactis and E. faecium (Sun et al 2011), and in artemia (Artemia urmiana) by B.subtilis and B. licheniformis (Ahmadnia Motlagh et al 2012). Similar results have also been reported in previous studies on prebiotics in fresh water crayfish (Cherax destructor) fed mannan oligosaccharides (MOS) (Sang et al 2011) and Caspian roach (Rutilus rutilus) fingerlings fed fructooligosaccharides (FOS) (Soleimani et al 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Aquat. Sci., 11 (1): 28-42, 2016 hemocytes (p<0.05) was also found in Cherax destructor which were fed by synbiotic diet (Sang et al, 2011). Another study reported that the hemocytes count decreased (p<0.05) after challenge test with Vibrio parahaemolyticus .…”
Section: Discussionmentioning
confidence: 78%
“…Dentro de los prebióticos más empleados se seleccionaron los MOS, dado que han sido ampliamente estudiados en especies de crustáceos cultivados, abordando su efecto sobre la fisiología, respuesta inmune, crecimiento y cambios en la morfología intestinal (Genc et al, 2007;Sang et al, 2009;Daniels et al, 2010;Sang & Fotedar, 2010;Mazlum et al, 2011;Sang et al, 2011Sang et al, , 2014Genc & Ebeoglu, 2013;Hoang & Jones, 2014). Otra consideración es su amplia disponibilidad comercial (AGRIMOS, Lallemand Animal Nutrition, Blagnac, France; MOS Fubon, Angel Yeast Angel Yeast Co., Ltd, Hubei, China continental; MOS, Hangzhou Gosun Biotech Co., Ltd, Zhejiang, China continental; Manano Oligosacaridos de Alta Calidad, Xian Shunyi BioChemical Technology Co., Ltd. Shaanxi, Xi'an, China continental; Bio-Mos, Alltech Inc, Nicholasville, KY, USA; YCW MOS, Tangshan Top Bio-Technology Co., Ltd, Hebei, China continental).…”
Section: Manano Oligosacáridos (Mos)unclassified
“…Algunas de las principales especies cultivadas a nivel mundial han sido objeto de estudio en cuanto a la suplementación dietaria con MOS y su impacto sobre la fisiología, patología y condiciones de cultivo. Las especies estudiadas abarcan desde camarones peneidos (Genc et al, 2007;Van Hai & Fotedar, 2009;Zhang et al, 2012;Genc & Ebeoglu, 2013;Sang et al, 2014) langostas australianas de agua dulce (Sang et al, 2009(Sang et al, , 2011 y langostas (Sang & Fotedar, 2010;Hoang & Jones, 2014).…”
Section: Mos En Acuicultura De Crustáceosunclassified
See 1 more Smart Citation